Parâmetros de fonte de sismos locais por inversão de formas de ondas - Zahradnik, Jiri (2010)
The main purpose of this work is to invert seismic waveforms in order to obtain moment tensor for two medium size earthquakes detected by OVSICORI-UNA Costa Rica permanent seismic network, occurred in 2004, following the mainshock of November 20 at 08:07 UTC (Mw=6.4 GCMT). The inversion for the focal mechanism is made using the package ISOLA (Zahradnik et al., 2005, Sokos & Zahradnik, 2008) and the seismicity are associated with a fault system that delineates the upper plate between the Caribbean plate and Panama Block. The obtained focal mechanisms are in agreement with results obtained by Pacheco et al. (2006) for this seismicity.